Synthesis, diffused reflectance and electrical properties of nanocrystalline Fe-doped ZnO via sol–gel calcination technique - Aydın, Cihat; M. S. Abd. El- Sadek; Zheng, Kaibo; Yahia, I. S; Yakuphanoğlu, Fahrettin (My University, 2012)
The nanocrystalline ZnO:Fe semiconductor oxides were successfully synthesized via the sol–gel calcination method. Structural, optical and electrical properties of the investigated samples were characterized by various techniques such as atomic force microscopy (AFM), UV–vis absorption and electrical transport measurements. The optical band gap for undoped ZnO (3.19 eV) decreases (2.75 eV) with increasing Fe-doped ZnO (20%). The temperature dependences of the electrical conductivities of undoped ZnO and Fe-doped ZnO were measured and analyzed by Arrhenius equation. The electrical conductivity of the samples decreases with the increase of Fe doping ratio; hence, the electrical conductivity mechanism is controlled by thermally activated processes. To support the nanostructure of Fe-doped ZnO, AFM micrographs were performed.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Fe-doped ZnO nanopowders; Sol–gel calcination method; Optical properties